More Active Mobility in Everyday Life: Finland Benefits from Reducing Car Use - Paloniemi, Riikka; Tuominen, Anu; Ahokas, Ira; Heikinheimo, Vuokko; Helminen, Ville; Karjalainen, Linda E.; Lindholm, Matti; Lyytimäki, Jari; Sundqvist, Henna; Tapio, Petri; Tiitu, Maija (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2023)
The Ministry of Transport and Communications’ National Programme for the Promotion of Walking and Cycling aims to increase the combined modal share of walking and cycling from the current 30% to 35–38% by 2030. In order to achieve the target, the current measures are not enough. Without more decisive action, the health, economic, and environmental benefits of increasing walking and cycling will remain a dream. Cities have a long tradition of car-based transport and urban planning. This is reflected in the reduced physical activity and, consequently, the decline in public health and increasing health care costs. While the car-centric lifestyle still prevails, there are weak signals of a shift towards more active, healthy, and sustainable mobility patterns: carlessness is becoming more common in dense and large cities. In the Oulu region, the popularity of cycling is significant compared to other urban areas in Finland. In Helsinki, the conditions for reducing car use have increased. According to the recent national studies measuring school children’s physical activity, children in urban areas are more active than those in rural areas. Behaviour change takes time. To bring about and consolidate change, we need to better understand people’s daily lives as well as create long-term plans across different sectors and levels of government to support active travel. This policy brief is the first in its series from the Healthy Lifestyles to Boost Sustainable Growth (STYLE) project, combining interdisciplinary knowledge on trends in transport and physical activity. Interpreting them through infrastructure and service designs and changing lifestyles, we generate insight on novel business opportunities and intervention models that induce physical activity. This provides innovative pathways towards current national policy targets and promotion of the societal vision. The project is funded by the Strategic Research Council at the Academy of Finland. Read more: www.styletutkimus.fi/en